TNC STRATEGIES: MERGERS AND ACQUISITIONS - Vovk, Svitlana (Journal of European Economy, 2017)
The paper presents the essence, the prerequisites of mergers and acquisitions; it singles out modern trends of mergers and acquisitions, namely the development of the social component of enterprise integration; also the operations are analyzed in merges and acquisitions throughout the whole world and in Ukraine, in particular.